شیکردنەوەی تواناسازی ژنان لەبەر ڕۆشنایی تیۆرە سۆسیۆلۆژیەکاندا تویژینەوەیەکی تیۆری شیکارییە - فرج, پ. د. نجاة محمد; محمد, م. ی باخان احمد (Sulaimani Journal for Humanities, 2023)
The current analytical theoretical study is an analysis of women's empowerment in view of sociological theories, which is conducted in Sulaimani City. Since ‘women's empowerment’ is one of the major issues of our contemporary society, it attempts to empower the women’s capacities in the psychological, social, economic, political and cultural areas. It helps women become self-reliant so that they can rely on themselves and face any difficulties in any situation. Because this process asserts the raising of women's awareness, women's readiness, women's self-confidence, it was assumed to be necessary to conduct a study on women's empowerment to demonstrate their roles in society on the basis of implementation their capacities. The core aims of our study are to try to conduct a theoretical analysis of women's empowerment according to sociological theories, as well as illustrating the most important features, principles and types of women's empowerment and also indicating women's empowerment in terms of social, psychological, economic, political, and cultural scopes. The most important findings of the study include: Women's empowerment does not only work on the economic or political or social or cultural aspects, but is related to all these aspects together. It is also related to social and intellectual progress and women's active self-realization in all different fields and proving their presence in society through improving and strengthening their abilities and capacities.